Excavations at Maisyan (2014) - Petrosyan, Levon; Khachatryan, Hamazasp; Yeganyan, Larisa (ARAMAZD: Armenian Journal of Near Eastern Studies, 2019)
Due to salvage actions realised in 2014 by the united expedition of the Institute of Archaeology and Ethnography and the Regional Museum of Shirak in the administrative district of the village Maisyan (Shirak region), six cist graves and one barrow were studied. The barrow has a cromlech of 14 m diameter, which is built of black stones and repeatedly reinforced using white limestone brought from the nearest hills. In one of two pit-graves opened under the barrow, the skeleton of the deceased was found with three vessels; in the other only vessels were present. Surely, both chambers belonged to the same person. Corresponding parallels are known from Lchashen and other sites dated to the first half of the 16th century BC – the transitional period from the Middle to the Late Bronze Age. In cist graves the burials were done using the rite of decarnation, or reburying, and date to the developed phase of the Iron Age (9th-8th centuries BC).